An update on the current training situation of German interns in oral and maxillofacial surgery at special times in 2021 - Pabst, Andreas; Goetze, Elisabeth; Thiem, Daniel G. E.; Bartella, Alexander K.; Seifert, Lukas; Beiglboeck, Fabian M.; Kröplin, Juliane; Hoffmann, Jürgen; Zeller, Alexander-N. (Journal of cranio-maxillofacial surgery, 2022)
The aim of this study was to evaluate the current state of training of German interns in oral and maxillofacial surgery (OMFS) under the influence of the COVID-19 pandemic in 2021. A previously tested questionnaire consisting of 53 questions was sent to interns in German OMFS (non-) university hospitals and private practices as an online survey. The questionnaire was adapted to current topics, such as the ongoing COVID-19 pandemic, aspects concerning nighttime and weekend services, overtime hours, surgical logbooks, benefits of academic degrees and support for scientific activities, part-time employment, parental leave and childcare. Next, results of questions from before the COVID-19 pandemic were re-evaluated. The COVID-19 pandemic influenced the clinical work (71.83%) and the current state of training (68.64%) in OMFS of most participants. Nighttime and weekend services are possible for employees in possession of only one degree (87.93% with a medical degree) in most hospitals. Not having one or both doctorate degrees was considered to be a disadvantage by 54.95%. In all, 42.11% of the participants attested to a positive influence of research on their training situation, and 50% reported financial or non-financial research support from the employer. Part-time employment was possible for 78.81% of the participants. The course of training was interrupted more often for women due to parental or maternity leave (10.53% of men and 30.95% of women). A total of 40.71% of the participants reported that childcare was available at the hospital, theoretically. The state of OMFS training in Germany can be referred to as positive. Current and future challenges are diverse, including aspects originating from the ongoing COVID-19 pandemic, gender aspects, reconciliation of family and work, and flexible working hours. Addressing these topics will ensure OMFS training at the highest surgical level and further increase interns’ satisfaction, preserving the specialty’s popularity and reception.
Gesehen am 28.06.2022